Asymmetric Relationship between Exchange Rate Volatility and Oil Price: Case Study of Thai-Baht - Harnphattananusorn, Supanee (International Journal of Energy Economics and Policy, 2022)
This paper aims to investigate asymmetric relationship between exchange rate volatility and oil price using a nonlinear auto-regressive distribution Lag (NARDL) developed by Shin et al. (2014). This technique allow us for estimating asymmetric long-run as well as short-run coefficients in a cointegration framework. For exchange rate volatility measurement, GARCH (1,1) model is applied. We use monthly data from January 2000 to June 2021. The results show that there are asymmetric impacts of oil price shocks on Thailand exchange volatility both in the long run and short run. Moreover, both positive and negative shocks on stock price index increase exchange volatility in the short run.